Respon Karakter Agronomi Cabai Rawit Lokal (Capsicum frutescens L.) terhadap Perlakuan Ekstrak Fitohormon Sebagai Upaya Domestikasi dalam Pemuliaan Tanaman - Angraeni Afrianti Una (Savana Cendana, 2020)
This study aims to determine the response of the agronomic character of the local island of Timor cayenne to the optimal concentration and frequency treatment of organic phytohormones. The study was conducted at the BBU (Balai Benih Unggul) TTU District Agriculture Office, JL. Eltari Km 6 Sasi Village, Kefamenanu City District, Timor Tengah Utara Regency in June to November 2019. This study uses a completely randomized design (CRD) with a 3x3 factorial pattern repeated 3 times. The first treatment is the concentration of organic matter with 3 levels, namely without the concentration of organic matter, the concentration of 45 ml / L water, the concentration of 95 ml / L water and the second treatment is the frequency of watering time which consists of 3 levels, namely 1 week, 2 weeks, and 3 weeks. The results showed that there was no interaction between phytohormone concentration and application time for each observation parameter. The results showed that the treatment of phytohormone concentration of 95 ml /L with watering once a week was able to increase the yield of timor local cayenne pepper plants.